Prenatal diagnosis of 20p13 microdeletion syndrome - Cem Yener; Cenk Sayın; Cihan İnan; Hakan Gürkan; Emine İkbal Atlı; Engin Atlı; Esra Altan; Sinan Ateş; Füsun Varol (Elsevier, 2021)
Objective: The objective of this study was to report the first case of prenatal diagnosis of the fetal 20p13 microdeletion syndrome in the literature. Case report: The mother was 31 years old and had a first trimester serum screening that indicated the fetus was at low risk. The prenatal ultrasound at 23 weeks of gestation showed mild ventriculomegaly (10.2 mm) and absent septum pellucidum. She underwent amniocentesis because of the abnormal imaging results. Karyotype analysis revealed normal results. Chromosome microarray analysis (CMA) was then performed to provide genetic analysis of the fetus and parents. CMA detected 317.902 kb deletion of 20p13 in fetus. Finally, pregnancy was terminated at 32 weeks of gestation. Conclusion: This study is the first to report the prenatal diagnosis of a 20p13 microdeletion syndrome. Our results further confirmed that genes in this region, including SOX12, NRSN2 are essential for normal fetal growth and TBC1D20 for normal brain development.